2021
DOI: 10.1093/bjsopen/zraa047
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence pattern of parathyroid adenomas

Abstract: Background Primary hyperparathyroidism (pHPT) is a common endocrine pathology, and it is due to a single parathyroid adenoma in 80–85 per cent of patients. Near-infrared autofluorescence (NIRAF) has recently been used in endocrine surgery to help in the identification of parathyroid tissue, although there is currently no consensus on whether this technique can differentiate between normal and abnormal parathyroid glands. The aim of this study was to describe the autofluorescence pattern of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
0
25
4
Order By: Relevance
“…To date, the research on the NIRAF characteristics of pathologic PGs has reported somewhat inconsistent findings. However, a number of studies have reported that pathologic PGs demonstrate lower AF compared to normal PGs 1,7,14,23,24 . This may be due to differences in the concentration of the fluorophore, which has not yet been identified, present in pathologic versus normal PGs.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…To date, the research on the NIRAF characteristics of pathologic PGs has reported somewhat inconsistent findings. However, a number of studies have reported that pathologic PGs demonstrate lower AF compared to normal PGs 1,7,14,23,24 . This may be due to differences in the concentration of the fluorophore, which has not yet been identified, present in pathologic versus normal PGs.…”
Section: Discussionmentioning
confidence: 98%
“…Finding and recognizing parathyroid glands (PGs) is a fundamental skill required for positive outcomes in both thyroid and parathyroid surgery. For thyroidectomy, this is the first step in preserving these glands, necessary to avoid postoperative hypoparathyroidism and hypocalcemia 1,2 . In parathyroidectomy, identifying the PGs is compulsory for surgical success.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations